Cycle lanes: their effect on driver passing distances in urban areas - Stewart, Kathryn; McHale, Adrian (Transport, 2014)
The current literature in the field of cycle lanes has often shown contradictory evidence as to the benefits and risks of cycle lanes and previous work has specifically shown that on higher speed roads, drivers may pass closer to a cyclist when a cycle lane is present. Utilising an instrumented bicycle, we collected information as to the passing distance demonstrated by drivers when overtaking a cyclist within the urban (30 mph/40 mph) environment. The presented analysis shows that when a driver encounters a cyclist mid-block (i.e. not at a junction), there are more significant variables than the presence of a cycle lane that determines the overtaking distance. The three most significant variables identified are: absolute road width, the presence of nearside parking and the presence of an opposing vehicle at the time of an overtaking manoeuvre. The analysis also demonstrated that there is a larger unknown factor when it comes to overtaking distances. We postulate that this unknown variable is the driver himself and will vary by area, site and even time of day (i.e. different driving cultures, congestion, or frustration during peak times, etc.) making it difficult to quantify.First Published Online: 22 Sep 2014